2011
DOI: 10.1089/scd.2010.0456
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells Secreting Angiopoietin-Like-5 Support Efficient Expansion of Human Hematopoietic Stem Cells Without Compromising Their Repopulating Potential

Abstract: Clinical and preclinical applications of human hematopoietic stem cells (HSCs) are often limited by scarcity of cells. Expanding human HSCs to increase their numbers while maintaining their stem cell properties has therefore become an important area of research. Here, we report a robust HSC coculture system wherein cord blood CD34 þ CD133þ cells were cocultured with mesenchymal stem cells engineered to express angiopoietin-like-5 in a defined medium. After 11 days of culture, SCID repopulating cells were expan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 30 publications
2
52
0
Order By: Relevance
“…Alternatively, supraphysiological concentrations of ANGPTL8 may induce b-cell proliferation, but this would be expected to cause hypertriglyceridemia. Other family members, including ANGPTL3, have been shown to promote proliferation of hematopoietic stem cells (32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, supraphysiological concentrations of ANGPTL8 may induce b-cell proliferation, but this would be expected to cause hypertriglyceridemia. Other family members, including ANGPTL3, have been shown to promote proliferation of hematopoietic stem cells (32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%
“…12,[20][21][22][23] However, as stated above, in addition to HSCs/MPPs, SRC activities were also found within LMPP fractions lacking erythro-myeloid differentiation potentials. 4,5 Furthermore, by comparing engraftment potentials of retrovirally marked baboon primitive haematopoietic cells in NOD/SCID mice and baboon, we previously provided evidence that cells other than true long term repopulating HSCs/MPPs are read out in the NOD/SCID xenotransplantation model.…”
Section: Discussionmentioning
confidence: 58%
“…8 In this context, we observed that HSPCs can neither be expanded nor maintained in conventional suspension cultures like IMDM supplemented with 10% FBS and SCF, TPO and FLT3-L (10 ng/ml each). 4,6 Since stromal cells have been reported to support maintenance and expansion of primitive haematopoietic cells with LTC-IC, NK-IC and SRC activities, [9][10][11][12] we tested whether these conditions are sufficient to truly expand HSCs/MPPs. To this end, we tested the haematopoietic support of conventional murine stromal cells and of mesenchymal stromal cells (MSC) raised from different human tissues.…”
Section: Introductionmentioning
confidence: 99%
“…MSCs promote expansion through cell-to-cell contact [114] and cytokine production [115]. Exogenous supplementation or forced expression of HSC-supportive factors in MSCs promotes ex vivo expansion of HSCs [116,117]. In a phase I clinical trial [118], a co-culture of HSCs with mesenchymal stromal cells proved to be safe in engraftment and led to an expansion of total nucleated cells and more rapid recovery of neutrophils and platelets than HSCs transplanted without co-culture.…”
Section: Hsc-mesenchymal Stromal Cell Co-culturementioning
confidence: 99%